Evaluation of triathlon suit characteristics relevant to thermophysiology of an athlete - Watson, C.; Nawaz, N.; Troynikov, O. (Proceedings, 2018)
The thermophysiological function of clothing influences athletic wellbeing and performance, particularly in outdoor endurance activities such as triathlon. However, there is very little existing research on the performance of triathlon suits relative to thermophysiological function of the wearer. This pilot study provides a benchmark for triathlon suit performance and insights into improving the suit design and material engineering. The study assessed the thermal and breathability attributes of 6 triathlon suits and concluded that while both of the attributes were similar overall, they varied in different body zones due to different design, construction and materials. Local thermal and evaporative performance were affected by fabric construction; double fabric layering in the stomach panel; the number, size, shape and material structure of rear pockets; cycle crotch pad size, shape and thickness; and panel design. The results of this study show the importance of garment design, construction and materials for the best thermal and evaporative resistance attributes of sportswear.